EFFECT OF WORK DISCIPLINE WORK EXPERIENCE AND SALARY ON EMPLOYEE PERFORMANCE AT PT. INDO SUGAR PASTIKA IN SRAGEN - Angora, Sofian Wahyu (Jurnal Ekonomi, 2020)
Human resources occupy a very strategic position in every business organization because humans are the main mover for the smooth production process and even the organization's running in order to achieve its goals. Once the importance of this human factor, then the issues of humanity in the company need to get attention from the management. The availability of potential and productive human resources in the context of increasing productivity is very important in the current era of industrialization. The purpose of this study is to determine whether work discipline, work experience, and salary have a significant effect on employee performance at PT. Indo Gula Pastika Sragen. The population in this study were employees of PT. Indo Gula Pastika Sragen. The sampling technique in this study is saturated sampling, namely taking the entire sample of 80 respondents. The research method uses multiple linear regression analysis using the F test, t test and dominant test with a significant level of 5%. The results of the study and the hypothesis show that work discipline, work experience and salary have a simultaneous effect with the results of multiple linear regression in the F test obtained Fcount of 159.674 greater than Ftable 2.72 while partially through t-test obtained tcount for each variable, namely Discipline Work (X1) is 5,849 Work Experience (X2) is 6,163 and Salary (X3) is 7,310 greater than the ttable value of 1,665, so the independent variables, namely Work Discipline, Work Experience and Salary have an effect on the dependent variable of Employee Performance. While the salary variable has a dominant effect on employee performance at PT. Indo Gula Pastika Sragen, and preferably the leadership of PT. Indo Gula Pastika Sragen can continue to maintain and even improve employee performance so that the main goal of the company can be achieved perfectly.